Understanding the path toward family economic well-being of coconut growers - Wijekoon, Rusitha; Sabri, Mohamad Fazli; Ahmad, Nobaya; Abd Rahim, Husniyah (Human Resource Management Academic Research Society, 2021)
Many countries are establishing national programs to increase their citizens’ family economic well-being. However, the concept of family economic well-being is still in its infancy, with only a few models established for developing countries. Thus, to create and implement effective policies, it is necessary to comprehend the concept family economic well-being from a multidisciplinary and multi-dimensional perspective, especially for a developing country like Sri Lanka. In the current study, path analysis was performed to examine the drivers that affect family economic well-being of coconut growers in Sri Lanka. Data from 400 respondents were analyzed empirically to validate the hypothesized relationships using the PLS-SEM approach. The findings provide support for the relationships between money attitude, technology adoption, financial behavior, financial knowledge, and family economic well-being which explained 91.2% of variance in family economic well-being. Understanding the paths that lead to better individual economic well-being has the potential to aid in successful policymaking, and curriculum design to assist individuals’ efforts to achieve greater family economic wellbeing.